2021
DOI: 10.1186/s12906-021-03286-2
|View full text |Cite
|
Sign up to set email alerts
|

Portulaca oleracea seeds’ extract alleviates acrylamide-induced testicular dysfunction by promoting oxidative status and steroidogenic pathway in rats

Abstract: Background Acrylamide (ACR) is a widespread industrial and food contaminant that garnered considerable attention for its carcinogenic, neurotoxic, and reproductive toxic effects. The antioxidant effects of Portulaca oleracea seeds extract (POS) and its fertility-enhancing effects were inspiring to evaluate the protective potential and pinpoint the mechanisms and molecular targets of the UPLC-MS fingerprinted POS extract on ACR-induced testicular toxicity in rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 48 publications
(24 reference statements)
6
23
0
Order By: Relevance
“…We observed that ACR exposure markedly reduced T, while LH and FSH prominently increased compared to control (Table 1). The hormonal dysregulation herein suggests adverse effect of ACR on testicular synthesis of T which has been reported in earlier publications (Abd‐Elsalam et al, 2021; Erdemli et al, 2019; Farag et al, 2021). However, the decreased T level implicates toxicity of ACR on T synthesis apparatus, including LH, FSH, 3β‐hydroxyl steroid dehydrogenase (3β‐HSD) and 17β‐HSD in the Leydig cells (Sharma et al, 2018).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We observed that ACR exposure markedly reduced T, while LH and FSH prominently increased compared to control (Table 1). The hormonal dysregulation herein suggests adverse effect of ACR on testicular synthesis of T which has been reported in earlier publications (Abd‐Elsalam et al, 2021; Erdemli et al, 2019; Farag et al, 2021). However, the decreased T level implicates toxicity of ACR on T synthesis apparatus, including LH, FSH, 3β‐hydroxyl steroid dehydrogenase (3β‐HSD) and 17β‐HSD in the Leydig cells (Sharma et al, 2018).…”
Section: Discussionsupporting
confidence: 76%
“…Acrylamide exposure is unavoidable due to global consumption of foods processed with high temperature (Farag et al, 2021). Acrylamide is formed during roasting, baking and frying; it is not basically formed in microwaved or boiled foods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress and its related events seem to be a potential mechanism involved in diabetes‐induced testicular damage. Researchers have found that a variety of antioxidants reversed the deterioration of testicular Leydig cells, Sertoli cells and spermatogenic cells induced by oxidative stress (Farag et al, 2021; Jiang et al, 2018; Khushboo et al, 2018; Zhou et al, 2020). Farag et al (2021) demonstrated that Portulaca oleracea seeds extract might provide a potential protective effect for acrylamide‐induced testicular dysfunction, mediated by its antioxidant effects.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that a variety of antioxidants reversed the deterioration of testicular Leydig cells, Sertoli cells and spermatogenic cells induced by oxidative stress (Farag et al, 2021; Jiang et al, 2018; Khushboo et al, 2018; Zhou et al, 2020). Farag et al (2021) demonstrated that Portulaca oleracea seeds extract might provide a potential protective effect for acrylamide‐induced testicular dysfunction, mediated by its antioxidant effects. These reports show that antioxidants can effectively reduce the accumulation of reactive oxygen species (ROS) and apoptotic cells in the testis while also promoting the integrity of the blood‐testis barrier, which can be regarded as an effective treatment strategy to prevent diabetes‐induced testicular damage.…”
Section: Introductionmentioning
confidence: 99%